Analisis struktur batuan berdasarkan data geolistrik tahanan jenis konfigurasi schlumberger dan konfigurasi dipole-dipole di Kecamatan Malalak Kabupaten Agam (Analysis of rock structures based on geoelectric resistance of schlumberger configuration and dipole-dipole configuration in Malalak District, Agam Regency ) - Winda Permatai Sari; - Akmam; - Hidayati (PILLAR OF PHYSICS, 2018)
The bedrock can interpreted using the Geolectrical method. The aim of this research was  determine the resistivity and structure of bedrock in Malalak District Agam area. This research used Dipole-dipole configuration and Schlumbergerconfiguration. Both of that configuration have complementary advantages and disadvantages to each other. The data were processed and interpreted with using Smoothness-Constraint Least Square inversion. The result of this research showed that type structure of bdrock in malalak Disctrict Agam area with Dipole-dipole configuration and Schlumberger configuration. The type structure of bedrock on this research is Clay, Sandstone, Limestone, Andesite andGranitee.